PENGGUNAAN TEKNOLOGI UNTUK MENINGKATKAN KETERLIBATAN ORANG TUA DALAM PENDIDIKAN ANAK - Suhartono, Tony; Cahyono, Heru (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2024)
This study aims to investigate the use of technology in increasing parental participation in educating children. In today's digital era, technological advances have resulted in various online applications and platforms that support communication between parents and schools, making it easier to exchange information and monitor children's development. This study uses a qualitative method that allows researchers to analyze the effectiveness of various technological tools in encouraging collaboration and communication. The results show that technology not only increases parental engagement, but also contributes to improved child learning outcomes. The increase in the frequency of communication between parents and teachers has a positive impact on children's learning motivation. However, it is important to note that not all parents have the same skills in using technology; Some are proficient, while others may have difficulties. Therefore, the implications of this study emphasize the importance of technology integration in school communication strategies by taking into account parents' technological capabilities, so that all parties can participate optimally in children's education. An inclusive approach in the use of technology is very important to support the role of parents in the development of children's education Keywords: Technology, Involvement, Parents, Children